Verification of P-Glycoprotein Function at the Dermal Barrier in Diffusion Cells and Dynamic "Skin-On-A-Chip" Microfluidic Device - Ágnes Bajza; Dorottya Kocsis; Orsolya Berezvai; András József Laki; Bence Lukács; Tímea Imre; Kristóf Iván; Pál Szabó; Franciska Erdő (MDPI AG, 2020)
The efficacy of transdermal absorption of drugs and the irritation or corrosion potential of topically applied formulations are important areas of investigation in pharmaceutical, military and cosmetic research. The aim of the present experiments is to test the role of P-glycoprotein in dermal drug delivery in various ex vivo and in vitro platforms, including a novel microchip technology developed by Pázmány Péter Catholic University. A further question is whether the freezing of excised skin and age have any influence on P-glycoprotein-mediated dermal drug absorption. Two P-glycoprotein substrate model drugs (quinidine and erythromycin) were investigated via topical administration in diffusion cells, a skin-on-a-chip device and transdermal microdialysis in rat skin. The transdermal absorption of both model drugs was reduced by P-glycoprotein inhibition, and both aging and freezing increased the permeability of the tissues. Based on our findings, it is concluded that the process of freezing leads to reduced function of efflux transporters, and increases the porosity of skin. P-glycoprotein has an absorptive orientation in the skin, and topical inhibitors can modify its action. The defensive role of the skin seems to be diminished in aged individuals, partly due to reduced thickness of the dermis. The novel microfluidic microchip seems to be an appropriate tool to investigate dermal drug delivery.